Mutations in Haemophilus influenzae Mismatch Repair Genes Increase Mutation Rates of Dinucleotide Repeat Tracts but Not Dinucleotide Repeat-Driven Pilin Phase Variation Rates - Bayliss, Christopher D. (American Society for Microbiology, 2004)
High-frequency, reversible switches in expression of surface antigens, referred to as phase variation (PV), are characteristic of Haemophilus influenzae. PV enables this bacterial species, an obligate commensal and pathogen of the human upper respiratory tract, to adapt to changes in the host environment. Phase-variable hemagglutinating pili are expressed by many H. influenzae isolates. PV involves alterations in the number of 5′ TA repeats located between the −10 and −35 promoter elements of the overlapping, divergently orientated promoters of hifA and hifBCDE, whose products mediate biosynthesis and assembly of pili. Dinucleotide repeat tracts are destabilized by mismatch repair (MMR) mutations in Escherichia coli. The influence of mutations in MMR genes of H. influenzae strain Rd on dinucleotide repeat-mediated PV rates was investigated by using reporter constructs containing 20 5′ AT repeats. Mutations in mutS, mutL, and mutH elevated rates approximately 30-fold, while rates in dam and uvrD mutants were increased 14- and 3-fold, respectively. PV rates of constructs containing 10 to 12 5′ AT repeats were significantly elevated in mutS mutants of H. influenzae strains Rd and Eagan. An intact hif locus was found in 14 and 12% of representative nontypeable H. influenzae isolates associated with either otitis media or carriage, respectively. Nine or more tandem 5′ TA repeats were present in the promoter region. Surprisingly, inactivation of mutS in two serotype b H. influenzae strains did not alter pilin PV rates. Thus, although functionally analogous to the E. coli MMR pathway and active on dinucleotide repeat tracts, defects in H. influenzae MMR do not affect 5′ TA-mediated pilin PV.